Bulgaria Systematic Country Diagnostic - World Bank (World Bank, Washington, DC, 2022)
The Systematic Country Diagnostic Update examines the key constraints to and opportunities for sustainably accelerating inclusive growth and boosting shared prosperity in Bulgaria. It builds on the first Systematic Country Diagnostic (SCD) published in 2015, entitled “Bulgaria’s Potential for Sustainable Growth and Shared Prosperity”. The analysis is organized in three components related to economic growth: strength, inclusiveness and sustainability. Although the earlier diagnostic remains valid for the most part, several contextual factors such as the health, social and economic repercussions of COVID-19, a drive to embrace the digital and green transformation, and a rapidly aging population— have emerged or gained prominence, creating new challenges or sharpening existing ones in all three growth areas. Alongside these mega-trends, institutions and governance continue to play a prominent role through their impacts on all segments of growth.